KEMAMPUAN PEMECAHAN MASALAH DITINJAU DARI METAKOGNISI PADA MODEL PROBLEM BASED LEARNING BERBANTUAN GOOGLE CLASSROOM - khunaeni, sirilivia; Scolastika Mariani; Putriaji Hendikawati (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2024)
Based on the results of interviews with teachers at SMP N 16 Semarang, it is known that in the learning process, students are not yet optimal in their mathematical problem solving abilities. This research aims to: (1) find out whether the Problem Based Learning learning model assisted by Google Classroom is effective on students' mathematical problem solving abilities, (2) find out the proportion of students' mathematical problem solving ability who obtain the Problem Based Learning model assisted by Google Classroom is higher than the proportion the mathematical problem solving ability of students who receive conventional learning, (3) knowing that the mathematical problem solving ability of students who receive the Problem Based Learning model assisted by Google Classroom is higher than conventional learning, and (4) whether there is an increase in students' mathematical problem solving ability after implementing Problem Based Learning model assisted by Google Classroom. The method used is mixed method sequential explanatory design. The research population was class VIII students at SMP Negeri 16 Semarang for the 2023/2024 academic year. The research subjects consisted of 6 students, namely 2 high, 2 medium and 2 low metacognition categories.